2022
DOI: 10.3390/app12178855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactic Acid Bacteria on Nutritional and Sensory Quality of Goat Organic Acid-Rennet Cheeses

Abstract: The aim of this study was to evaluate the applicability of selected Lactobacillus strains, previously isolated from spontaneously fermented foods, as starter cultures in the production of organic dairy products—acid-rennet goat’s cheeses under industrial conditions. The basic composition and the effect of starter cultures on the physicochemical, microbiological, sensory as well textural properties during the production and storage of goat’s cheese were evaluated. Lactic acid bacteria count in cheese samples wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Lactose in milk is transformed into lactic acid due to lactic acid bacteria fermentation. The accumulation of lactic acid reduces pH, protects against the growth of unwanted microbes, and contributes to syneresis [74]. Reducing the pH of milk has the most profound implications for micellar calcium phosphate dissolution, casein net charge decrease, and casein dissociation from micelles [75].…”
Section: Physicochemical Properties and Yield Of Cheesementioning
confidence: 99%
See 2 more Smart Citations
“…Lactose in milk is transformed into lactic acid due to lactic acid bacteria fermentation. The accumulation of lactic acid reduces pH, protects against the growth of unwanted microbes, and contributes to syneresis [74]. Reducing the pH of milk has the most profound implications for micellar calcium phosphate dissolution, casein net charge decrease, and casein dissociation from micelles [75].…”
Section: Physicochemical Properties and Yield Of Cheesementioning
confidence: 99%
“…In a study by Sakr et al [79], the addition of calcium chloride to milk at a level of 200 mg 100 mL −1 resulted in Karish cheese with a pH of 4.69, while the addition of 300 mg 100 mL −1 calcium chloride lowered the pH of the cheese to 4.50. Kajak-Siemaszko et al [74] reported the pH value of fresh acid rennet cheese made from goat's milk from 5.86 to 6.16, depending on the starter culture used. However, Dmytrów et al [80] measured the pH of acid goat cheese at 4.7.…”
Section: Physicochemical Properties and Yield Of Cheesementioning
confidence: 99%
See 1 more Smart Citation